THE IMPACT OF COMBINED ECOLOGICAL STRESS ON THE ENZYMATIC STATUS OF BLOOD AND PANCREATIC TISSUE (Multidisciplinary Journal of Science and Technology, 2026)
The article is devoted to studying the patterns of changes in the body's enzyme homeostasis under the influence of combined ecological and lifestyle stress (ecostress), which includes hypokinesia, high-temperature exposure, and intense insolation. A detailed analysis of the activity of key hydrolytic enzymes —